Initial Development and Testing of an Adaptive Mission Planner for a Small Unmanned Underwater Vehicle - Arrieta, Richard M.; Farrell, Jay A.; Li, Wei; Pang, Shuo (2003)
An Adaptive Mission Planner (AMP) was developed for the REMUS Unmanned Underwater Vehicle (UUV) in order to have the vehicle react to real-time sensor data and alter course for the purpose of chemical plume tracing. In order for a UUV to track a plume autonomously, it must implement search strategies in an intelligent manner as dictated by environmental circumstances without human intervention. Throughout the mission, the UUV will combine the sensed flow and concentration information to construct a map of likely source or plume locations. This AMP has been designed and tested in simulation at the University of California, Riverside, and has now been installed on the SPAWARSYSCEN-SD REMUS UUV. This paper will describe the search strategies and initial field tests which use the AMP to break away from the vehicle's pre-programmed missions. Two sets of experiments are described herein. The first uses bathymetry as the environmental driving input. The second uses chemical concentration as the primary input. Presented at the International Conference on Offshore Mechanics and Arctic Engineering (OMAE 2003) (22nd) held in Cancun, Mexico on June 8-13, 2003. The original document contains color images.